Study of epidemiology, management and outcome of acute kidney injury post noncardiac surgery over 12 months at Groote Schuur Hospital, Cape Town - Mzingeli, Luvuyo (Department of Medicine, 2016)
INTRODUCTION : Acute kidney injury (AKI) is a disorder that is defined by rising serum creatinine and reduced urine output. It occurs in approximately 1-7% of hospitalized patients and is a major predictor of morbidity and mortality. It increases the costs and duration of hospital stay. AKI has been extensively studied post cardiac surgery, but there has been little attention on AKI occurring after non cardiac surgery . There have been few studies on AKI from developing countries and a paucity of data of post non cardiac surgery AKI. OBJECTIVE : To identify which known risk factors for AKI are commonly encountered at Groote Schuur Hospital, to document 30 and 90 day mortality, length of hospital stay, recovery of renal function at 90 days and identify factors associated with outcome post non-cardiac surgery. DESIGN: Prospective observational study. SETTING: Surgical Wards and ICU. PARTICIPANTS: Patients with AKI post non-cardiac surgery admitted between July 2012 and July 2013, who were 18 years and above without underlying stage 5 chronic kidney disease. OUTCOME MEASURES: Mortality, identification of risk factors, length of hospital stay and recovery of renal function. RESULTS: Of 367 patients referred to renal unit with AKI, 60 patients met inclusion criteria. Patients had an average age of 52.8 years (standard deviation 16.6) and 70% (42/60) were male. 61.7% (37 /60) were Coloured, 20% (12/60) were White and 18.3% (11/60) were Black. These patients were exposed to the following risk factors: 80%(48/60) had emergency surgery, 66. 7%(40/60) had sepsis, 65%(39/60) had perioperative contrast exposure, 53.3%(32/60) had hypotension that required inotropic support in 50%(30/60). Mortality was 33.3% (20/60) at 30 days and 45% (27/60) at 90 days. Of the 33 patients who did not die, 81.8% (27 /33) recovered their renal function to normal baseline creatinine at 90 days. Of the 6 patients, whose renal function did not return to baseline, none required long term dialysis. Perioperative contrast exposure was associated with a longer median length of hospital stay compared to patients not exposed to contrast (21 vs 16 days respectively, p<0.05). Sepsis and age > 60 years was associated with poor recovery of renal function (p=0.005, p=0.01 respectively). No risk factor was identified to be associated with mortality. CONCLUSION: Risk factors for post non cardiac surgery AKI commonly encountered at Groote Schuur Hospital were emergency surgery, sepsis, hypotension, perioperative use of inotropes and perioperative contrast exposure. The latter was identified as a modifiable risk factor which significantly prolonged hospital stay. Sepsis and age > 60 years were associated with poorer recovery of renal function.